209k views
3 votes
Prove that (Cos A +cosB)^2+(SinA+sinB)^2=4cos^2(A-B/2)


User Algiz
by
5.4k points

1 Answer

5 votes

Answer:


(cosA + cos B)^2 + (sin A +sinB)^2 \\\\= cos^2A + cos^2B + 2cosA cosB + sin^2A +Sin^2B +2sinAsinB\\\\=(cos^2A + sin^2 A) + (cos^2B +sin^2B) +2cosAcosB + 2sinAsinB\\\\= 1 + 1 + 2cosAcosB + 2sinAsinB\\\\=2 + cos(A+B)+cos(A-B) + cos(A-B) -cos(A+B)\\\\=2 + 2cos(A-B)\\\\=2(1 + cos(A-B))\\\\=2* 2 cos^2((A-B)/(2))\\\\=4cos^2((A-B)/(2))

Hence proved .

User Nathan Bubna
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.